Measuring the Information Needs of Teachers in their Organizational Context: A Preliminary Adaptation Study for the Portuguese Population - Lobo, Fátima; Hargie, Owen (European Journal of Social Science Education and Research, 2020)
There has been a dearth of research into the role of organizational communication within the teaching context in general, and in Portugal in particular. One reason for this has been the lack of suitable measurement instruments. The present study is intended to help to rectify this situation by adapting to the Portuguese population two questionnaires that integrate related communicational items: Information I receive now / Information I need to receive, and Information I send now / Information I need to send. These were based on instruments previously validated in the UK and USA, and were adapted to the Portuguese context through a process of translation-retroversion, maintaining the structure and number of items. Subsequently, data were collected on a population of teachers from three schools in Northern Portugal. The instruments revealed robust psychometric qualities as well as readily transferrable comprehension and applicability. They are therefore pertinent instruments that offer real potential for future research. The results also reveal significant differences between the ‘information received’ and the ‘information that needs to be received’, as well as the ‘information sent’ and the ‘information that needs to be sent’, by teachers within their schools. From a practical point of view, this research allows us to rethink organizational communication strategies and thus to contribute to the promotion of approaches capable of enabling diagnosis and intervention in this field. This, in turn, will contribute to the development of strategies that are capable of promoting the well-being and quality of life of teachers.